Prinsip dan Batasan Monopoli pada Prilaku Ihtikar dalam Pandangan Islam - Dheddy Abdi Tamba; Nurrohman; Ihwan Sugiarto; Ari Fajar Santoso; Heri Budi Harsono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Hoarding in Islam is known as ihtikar, meaning hoarding behavior, which is one part of monopolistic practices. This hoarding behavior hurts the supply of goods in the market, so it can cause instability in the availability of goods and demand for goods and can result in market distortions. This research uses normative juridical, with a qualitative approach based on library research. Many business actors conduct monopolies by setting higher prices; according to business law in Indonesia, such monopolistic practices are strictly prohibited. In Islamic law, monopoly is allowed under restrictions and provisions based on the Koran and Hadith. Monopolies are permitted as long as they do not carry out hoarding (Ihtikar), especially goods that become staple foodstuffs or are related to the livelihood of many people. The role of government is to control monopolies and maintain stability by making regulations and direct intervention.